Should we prioritize proton beam therapy before making a decision on orthotopic liver transplantation for unresectable hepatoblastoma? - Hsiao, Yi-Wen; Wang, Yi-Lun; Tseng, Chen-Kan; Chang, Tsung-Yen; Chen, Shih-Hsiang; Jaing, Tang-Her (The Turkish Journal of Pediatrics, 2026)
Background. In unresectable hepatoblastoma (HB), particularly “pre-treatment extent of tumor” (PRETEXT) IV tumors or those with positive annotation factors, standard management consists of intensive chemotherapy followed by surgical resection or orthotopic liver transplantation (OLT). Radiotherapy has traditionally been avoided because of the liver’s radiosensitivity and the risk of radiation-induced liver disease. Proton beam therapy (PBT), owing to its dosimetric advantage and ability to spare uninvolved liver parenchyma, may represent a potential local control strategy in selected pediatric patients for whom curative surgery or OLT is not feasible. Case Presentation. We describe five pediatric patients with advanced hepatoblastoma treated with proton beam therapy at our institution between February 2022 and January 2024. The cohort included three girls and two boys, with a median age of 3.0 years (interquartile range [IQR], 1.6–4.0) and a median alpha-fetoprotein level of 435,453 ng/mL (IQR: 7,668–1,276,681) at diagnosis. All patients were initially considered inoperable because of extensive hepatic involvement, inadequate future liver remnant, or multifocal disease, and OLT was not feasible owing to donor limitations or medical comorbidities. All received neoadjuvant chemotherapy using SIOPEL-based regimens, achieving partial tumor response. Tumors ranged from 5 to 12 cm and involved central hepatic segments, the portal region, or both lobes. PBT was delivered at a total dose of 50 GyE in 10–25 fractions as definitive or consolidative therapy, followed by surgical resection in three patients. Two patients additionally received targeted therapy and immunotherapy. At last follow-up, four patients were alive with no evidence of disease, while one patient died from tumor progression. Conclusions. These cases suggest that proton beam therapy may serve as a feasible liver-sparing local treatment option for selected pediatric patients with unresectable or residual hepatoblastoma when surgery or OLT is not possible. While limited by availability and cost, PBT may facilitate multimodal therapy and preserve future treatment options.